2012
DOI: 10.1007/s13224-011-0070-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oxidative Stress Biomarkers and Antioxidant Enzymatic Activity in Male Infertility of North-East India

Abstract: Introduction Oxidative stress is a common pathology seen in approximately half of all infertile men. In a normal situation, the seminal plasma contains antioxidant mechanisms which are likely to quench these reactive oxygen species. However, during infertility complications these antioxidant mechanisms may downplay and create a situation which is called oxidative stress.Objective The aim of the present study was to assess the levels of lipid peroxide (LPO), protein peroxide (PPO) and activities of antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
2
9
0
2
Order By: Relevance
“…This excessive LPO impairs the antioxidant defence system in the male reproductive tract and leads to male infertility [72] . Results obtained in this investigation showed higher MDA concentration in the blood plasma of infertile men were similar with another Indian population study where blood and semen LPO levels were correlated positively [73] , hence smoking and alcohol exposure could be associated with elevated LPO levels. Shiva et al described that high MDA levels were associated with low sperm concentration, motility, morphology and related to poor sperm quality, hence sperm membrane integrity [23] .…”
Section: Resultssupporting
confidence: 89%
“…This excessive LPO impairs the antioxidant defence system in the male reproductive tract and leads to male infertility [72] . Results obtained in this investigation showed higher MDA concentration in the blood plasma of infertile men were similar with another Indian population study where blood and semen LPO levels were correlated positively [73] , hence smoking and alcohol exposure could be associated with elevated LPO levels. Shiva et al described that high MDA levels were associated with low sperm concentration, motility, morphology and related to poor sperm quality, hence sperm membrane integrity [23] .…”
Section: Resultssupporting
confidence: 89%
“…Another recent study demonstrated that catalase exerts a protective role to restore sperm quality (9,10). In agreement with these findings, some studies have reported the differential expression of antioxidant enzymes between fertile and infertile men (11)(12)(13). Consistent with these evidences, our previous proteomic study demonstrated that the sperm proteome changes during capacitation, which is one of the fundamental processes that spermatozoa undergo to acquire the ability to fertilize an egg (14).…”
Section: Introductionsupporting
confidence: 83%
“…In normozoospermic men, higher seminal activities of enzymatic antioxidants correlate with lower total malondialdehyde levels (MDA), indicating the protective effect of these antioxidants against oxidative stress-induced lipid peroxidation [ 133 , 134 ]. Conversely, infertile men with poor spermatozoa quality have lower levels of seminal enzymatic antioxidants that correspond with increased levels of lipid peroxidation [ 133 , 135 ].…”
Section: Antioxidants As Ameliorating Agentsmentioning
confidence: 99%